Histopathological Assessment of Dental Fluorosis - Kashif Adnan, Mujtaba Shabir, Syed Muhammad Hamza Riaz, Dinesh Kumar, Fatima Siddiq, Sana Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to conduct a comprehensive histopathological assessment of dental fluorosis across varying levels of severity and establish correlations with observable clinical symptoms. The research also examines the relationship between fluoride concentration and the extent of fluorosis, contributing to the understanding of this oral health concern. Study Design: Secondary data analysis Methods: In order to analyze quantitative data on dental fluorosis from reliable resources like PubMed and specialized journals, the research approach used SPSS. By PRISMA principles, we also consulted grey literature for information. Descriptive statistics provided initial insights after data cleansing. Pearson's correlation revealed relationships between the severity of dental fluorosis and histological alterations. These correlations were subsequently analyzed using multiple regression techniques. A one-way ANOVA was used to analyze geographic variations in symptoms, and a meta-analytic technique guaranteed the accuracy of the data. Results: The findings underscore the strong correlation between elevated fluoride levels and heightened fluorosis severity, aligning with previous research in the field. The study emphasizes the necessity of effective fluoride regulation and monitoring in water sources to prevent the development of fluorosis. These insights hold implications for dental practices and public health strategies, necessitating community education on fluoride sources and enhanced diagnostic and treatment approaches by healthcare professionals. Conclusion: The study's outcomes underscore the significance of empirical research in enhancing public health initiatives and shaping preventive interventions. By focusing on longitudinal investigations, geographically comparative studies, and meticulous risk assessments, future research can contribute to a more nuanced understanding of fluorosis and facilitate evidence-based preventive measures. Implementing these recommendations will aid in improving our comprehension of fluorosis, safeguarding community health, and empowering individuals to make informed decisions regarding fluoride exposure. Keywords: Dental fluorosis, Fluoride concentration, Histopathological assessment, Severity, Public health initiatives.